2006
DOI: 10.1007/s00284-005-5578-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Plant Defense Enzymes and Phenolics by Treatment With Plant Growth–Promoting Rhizobacteria Serratia marcescens NBRI1213

Abstract: In greenhouse experiments, plant growth-promoting rhizobacteria (PGPR) Serratia marcescens NBRI1213 was evaluated for plant growth promotion and biologic control of foot and root rot of betelvine caused by Phytophthora nicotianae. Bacterization of betelvine (Piper betle L.) cuttings with S. marcescens NBRI1213 induced phenylalanine ammonia-lyase, peroxidase, and polyphenoloxidase activities in leaf and root. Qualitative and quantitative estimation of phenolic compounds was done through high-performance liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(63 citation statements)
references
References 19 publications
3
59
0
1
Order By: Relevance
“…As tea plants are cultivated for their leaves from which the beverage is made, an increase in leaf number is considered to be of importance to the tea industry. In an early study, S. marcescens NBR11213 was reported to induce plant growth promotion and biological control of foot and root rot of betelvine caused by Phytophthora nicotianeae (Lavania et al 2006). Guo et al (2004) also reported that three strains of PGPRs Á Serratia sp.…”
Section: Discussionmentioning
confidence: 99%
“…As tea plants are cultivated for their leaves from which the beverage is made, an increase in leaf number is considered to be of importance to the tea industry. In an early study, S. marcescens NBR11213 was reported to induce plant growth promotion and biological control of foot and root rot of betelvine caused by Phytophthora nicotianeae (Lavania et al 2006). Guo et al (2004) also reported that three strains of PGPRs Á Serratia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Hence enhanced lignification and phenolics are the most important molecular events during fungal evasion of host defense mechanisms (Walters et al 2005). The inductions were achieved by using excellent elicitors like chemicals (Silué et al 2002), biocontrol agents (Lavania et al 2006), plant extract (Guleria & Kumar 2006) and fungicides (Molina et al 1998). Normally, the induced lignification is reflected by enhanced enzyme activities and phenol.…”
Section: Introductionmentioning
confidence: 99%
“…Serratia marcesscen 90-166 mengurangi serangan Cucumber Mosaic Virus pada tomat dan mentimun (Raupach et al,1996), juga mengurangi gejala penyakit antraknos dan layu fusarium pada mentimun (Liu et al,1995). Bakterisasi dengan Serratia marcescens NBRI1213 meningkatkan aktifitas enzim Peroksidase pada daun dan akar tanaman sirih yang tahan terhadap Phytopthora nicotiana (Lavania et al, 2006).…”
Section: Hasil Dan Pembahasanunclassified